A TAXING TIME OF YEAR FOR NEW YORK (Tufts Archival Research Center, 2007)
Advertisment against a raise in New York cigarette taxes. States that New Yorkers pay higher taxes than most people do and that the New York treasury has surplus money. Accuses such a tax raise of being unfair.